Analisis Ketidaksesuaian Produk Air Minum dalam Kemasan di PT Amanah Insanillahia - Elita Amrina; Nofriani Fajrah (Jurnal Optimasi Sistem Industri, 2015)
Nowadays, the development of industry is increasing very rapidly. It can be known as the high competition between companies. Not only large and international scaled companies, small and medium-sized companies are also facing the same challenges in the global competition. Therefore, the companies need to conduct a quality control to maintain the quality of products produced and to achieve the conformance to specifications of product that has standardized by the company policies in order to improve the customer satisfaction. PT Amanah Insanillahia is a company involved in the bottled water industry. Based on the preliminary study, it shown the quality control only conducted to check the number of defective products produced without further evaluation and analysis. Therefore, there is a need to analyze the data of defective products produced and evaluate the results. The purpose of this study is to analyze the nonconformity product of the bottled water 600 ml brand PRIM-A. The p-chart is used in this research to analyze the number of defective products. Then, the fishbone diagram is used to analyze the causes of defective products. The results show that there is no data out of the control limits and mostly the data near in the central line of the p-chart. Using the fishbone diagram, it concluded that factors of man, machines, materials, methods, and environment are the causes of nonconformity products of the bottled water 600 ml brand PRIM-A. It is hoped this study will beneficial for the company to improve the product quality as well as to increase the customer satisfaction.